Heurísticas, vieses e arquitetura de escolha: análise da relação entre comportamentalismo econômico e regulação - Montenegro, Lucas dos Reis (2022)
Freedom of choice is a subject that dwells among mankind’s imagination since its dawn. Rationality, that is, the attribute of being ration, as well. Human rationality is taken as the element that differentiates us humans from other species. It is by the assumption of rationality that Economics elaborates its models of behavior prediction – the Rational Choice Theory. The paradigm of rationality has been questioned by the adepts of behavioral economics. Human beings are not as rational as Rational Choice Theory would agree, which challenges the ideal form o Homo Economicus as envisioned by Economics. In which way could Behavioral Economics relate to the Theory of Regulation? This work defends that this relationship is twofold: as a justification on why regulate and as a regulatory strategy. Those capacities, however, are not free from criticisms: the first capacity has a risk of theoretical banality; the second faces criticisms in regard of its ethics. This work’s mission, so, is to ground Behavioral Economics – in a reasonable form, without unnecessary enthusiasm – a one of Brazil’s Theories of Regulation.